2021
DOI: 10.12688/f1000research.54390.1
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer incidence trends in the United States from 2000-2017: Analysis of Surveillance, Epidemiology and End Results (SEER) database

Abstract: Background: Recent incidence trends of pancreatic cancers were reviewed by demographics and histologic type to observe any new findings. Methods: Data was used from the Surveillance, Epidemiology, and End Results (SEER) registry 18 (2000-2017) and it underwent temporal trend analysis. Pancreatic cancer incidence rates were reported based on histological subtype and demographics. Results: The incidence rate of white males increased significantly during 2000-2017 (annual percent change (APC) = 3.5%) compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…With an ever increasing incidence year on year [ 5 ], PDAC remains one of the few tumour entities sharing an extremely poor prognosis with an overall 5-year survival rate of 5–10% [ 4 ]. While surgical resection and adjuvant chemotherapy remain indispensable for curative treatment, targeted therapies have been failing to improve patient outcome and long-term survival markedly and, therefore, could not be successfully introduced to the clinical setting of PDAC treatment so far [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an ever increasing incidence year on year [ 5 ], PDAC remains one of the few tumour entities sharing an extremely poor prognosis with an overall 5-year survival rate of 5–10% [ 4 ]. While surgical resection and adjuvant chemotherapy remain indispensable for curative treatment, targeted therapies have been failing to improve patient outcome and long-term survival markedly and, therefore, could not be successfully introduced to the clinical setting of PDAC treatment so far [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…With a persistently rising incidence, pancreatic ductal adenocarcinoma (PDAC) is currently the seventh leading cause of malignoma-related death and is estimated to become the second leading cause of fatalities associated with cancer in 2030 [ 1 , 2 ]. Termed as one of the “recalcitrant” cancers by US legislation [ 3 ], PDAC overall 5-year survival rates remain poor ranging from 5–10% with 80–85% of the patients diagnosed in an advanced or metastatic stage of the disease [ 4 , 5 ]. Further, surgical resection supplemented by an adjuvant chemotherapy remains the only curative therapy approach, whereby only 20% of the patients with localised PDAC reach postoperative 5-year survival [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…and "Suspicious" cases were also excluded due to lack of definitive diagnosis and inter-observer variability. Rarely, some cell blocks from such cases were included in the negative category if they met one of two criteria: (1) The original pathology report described them as negative or unremarkable; (2) They were cleared in blinded review by our senior expert cytopathologist (X.L. ).…”
Section: Data Collection and Annotationmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is an aggressive type of cancer derived from the epithelial cells that make up the ducts of the pancreas. PDAC ranks firmly last among all cancer types in terms of worst prognostic outcomes 1 , and its incidence and mortality rates have continued to increase for decades in Unites States [2][3][4][5] . According to one study 6 , from 1990 to 2017, the number of cases and deaths worldwide identified as related to pancreatic carcinoma doubled.…”
Section: Introductionmentioning
confidence: 99%
“…PAAD is prone to distant metastasis, with a high degree of malignancy and poor prognosis, and the 5-year survival rate is only 7.2% ( He et al, 2022 ). Despite great advances in the treatment of PAAD over the past decades, regrettably, the incidence and mortality of this disease have increased worldwide, especially in countries such as the United States, China, and Brazil ( Ali et al, 2021 ; Chaves et al, 2022 ; Yin et al, 2022 ). Recent projections suggest that by 2030, PAAD could surpass colorectal cancer as the second leading cause of cancer-related death after lung cancer ( Ali et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%